‘FELIX CONVERSUS EX MANICHAEIS’: A CASE OF MISTAKEN IDENTITY - Lieu, Samuel (The journal of theological studies, 1981)
JUDITH, SAMUEL LIEU; ‘FELIX CONVERSUS EX MANICHAEIS’: A CASE OF MISTAKEN IDENTITY, The Journal of Theological Studies, Volume XXXII, Issue 1, 1 April 1981, Page